Evaluating the Rationale for Folding Wing Tips Comparing the Exergy and Breguet Approaches - Hayes, D.; Lone, Mudassir M.; Whidborne, James F. (AIAA, 2017)
The design and development processes for future aircraft aims to address the environmental and efficiency challenges needed to facilitate the engineering of concepts that are far more integrated and require a multidisciplinary approach. This study investigates the benefit of incorporating span extension wing tips onto future aircraft configurations as a method of providing improved aerodynamic efficiency, whilst allowing the extension to fold on the ground to meet airport gate size constraints. Although the actuated wing tips are not studied in detail, the focus of this study is to compare two different methods of analysis that can be used to identify the benefit and limitations of adding such devices. The two methods considered are a quasi-steady implicit energy analysis based on the Breguet Range Equation and an explicit energy analysis based on the first and second laws of thermodynamics known as Exergy Analysis. It has been found that both methods provide agreeable results and have individual merits. The Breguet Range Equation can provide quick results in early design, whilst the Exergy Analysis has been found to be far more extensive and allows the complete dynamic behaviour of the aircraft to be assessed through a single metric. Hence, allowing comparison of losses from multiple subsystems.